Assessment of anti-tyrosinase, anti-elastase and anti-acetylcholinesterase properties of fermented mango leaves at different maturity level - Nur Diyana A.; Koh, S.P.; Aziz N.; Hamid N.S.A.; Abdullah R.; Puteh F.; Sarah S. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Mango leaves are known to possess many health benefits but the industry only focused on mango fruit production, resulting in abundant leaves being underutilized. In this study, we managed to transform mango leaves into a new fermented drink, which has a pleasant taste through the bio-fermentation process. Different maturity levels of mango leaves were selected; premature leaves (light brown, LBML), intermediate mature leaves (light green, LGML) and mature leaves (green, ML), which were subjected to a fermentation process using bacteria and yeast. Tannin content, organic acids profile and various enzymes functionality activities (e.g. inhibition of tyrosinase, elastase and acetylcholinesterase) studies were determined on fermented mango leaves drink. The reduction of tannins content in all fermented mango leaves resulted in a less astringent taste as a consequence of the microbial action to break down tannins. Acetic, oxalic, kojic and quinic acid are some of the organic acids detected in fermented mango leaves that contributed to its slightly acidic taste. In comparison to non-fermented mango leaves, all fermented samples, particularly LBML drink showed a significant improvement (P<0.05) in tyrosinase inhibition (87.96%). Fermented mango leaves also exhibited good inhibition activity towards elastase (>80%) and acetylcholinesterase (>90%). Further histopathology examination on various rat’s organs (kidney, liver, spleen, and stomach) showed no sign of inflammation symptoms. Through limit toxicological evaluation, the safety consumption rate (IC50 value) for fermented mango leaves was 1000 mL/50 kg of human bodyweight. The improvement functionality activities of fermented mango leaves with a higher inhibition rate against tyrosinase, elastase, and acetylcholinesterase indicate its great potential as a food remedy for anti-ageing treatment.